Language variation and change in Al-Karak Governorate (Jordan) - Al-Shamayleh, Tamadur Sulayman (International Journal of Psychosocial Rehabilitation, 2020)
This research explores language variation and change in the speech of nonstandard Arabic in Al-Karak Governorate (a city in the south region in Jordan). There are three phonological variables which are explored; /ʤ/, /q/, and the insertion of /i/. These features are studied in relation to two social variables; age and gender. The sample consists of 40 inhabitants from this district ( 20 males and 20 females) from two age groups ; middle (18-45) and old (45+). The data were collected through sociolinguistic interviews and they have been analyzed within the frame work of the Variationist Paradigm. The results reveal that there are considerable variation and changes regarding the selected linguistic variables. Moreover, the study reveals that age and gender play a great role in such variation. The young generation ( mainly females) in Jordan is the leaders of this change.